The analysis of structural elements of productivity and other quantitative characteristics of rice samples - P. I. Kostylev; E. V. Krasnova; A. V. Aksenov; L. M. Kostyleva; A. G. Galayan (Зерновое хозяйство России)
The analysis of structural elements of productivity and other quantitative characteristics of rice samples To develop highly productive varieties it’s essential to select middle-high plants that are able to produce thick stand with a slight decrease of weight and number of kernels per panicle. Therefore it’s necessary to be aware of the optimal values of quantitative characteristics of rice samples which facilitate the formation of maximum productivity of the best genotypes in the definite soil-climatic conditions. The article presents the results of the analysis of productivity of rice samples approved to competitive variety-testing in 2016-2017 in plant height, number of spikelets and kernels per panicle, 1000-kernel weight, number of productive stems. It has been determined that in 2016 rice productivity ranged from 5.89 to 9.43 t/ha (in average 8.35); in 2017 it ranged from 6.13 to 9.44 t/ha (in average 7.73). The standard variety “Uzhanin” produced 8.48 t/ha in 2016 and 7.23 t/ha in 2017. The conducted correlation analysis of 64 rice samples allowed establishing correlation of structure elements with productivity. The samples with such characteristics as 95-100 sm of plants, 90-96 days of the period “sprouts-flowering”, 360-380 productive stems per 1 m2, 100-115 and 130-135 kernels per panicle and 28-30g of 1000-kernels weight showed their maximum productivity in 2016. In 2017 the most productive samples were the plants of 95-100 sm, 95-97 days of the period “sprouts-flowering”, 360-400 productive stems per 1 m2, 95-110 and 125-130 kernels per panicle and 28g of 1000-kernels weight.